Analyze Flipbook-Based Interactive Learning Management Survey Conducted by Teachers on Elementary School Students - Nafiah, Nafiah; Sri Hartatik; Pance Mariati; Katrina Dwi Novira Rahmayanti; Sukma Prabawati (Jurnal Pendidikan Anak, 2024)
This study investigates the extent to which elementary school teachers implement digital-based learning management using flipbook applications. As the educational landscape rapidly shifts towards the integration of technology, interactive tools like flipbooks are gaining attention for their potential to enhance learning outcomes by making content more engaging and visually appealing. However, there is limited research on the adoption of flipbook-based digital learning management in schools. This study addresses this gap by conducting a survey involving 378 elementary school teachers. The research employs a descriptive quantitative method, utilizing an online questionnaire distributed via Google Forms to gather data on teachers' familiarity with, experience in designing, and implementation of digital learning using interactive flipbooks. The findings reveal that 33.07% of the respondents are not familiar with flipbook-based digital learning management, with only a small percentage (7.67%) indicating high familiarity. The survey also highlights that 45.50% of teachers have never designed digital learning management using interactive flipbooks, and 67.20% have never implemented it in the classroom. Despite the recognized benefits, such as improved student engagement and motivation, the results suggest a considerable gap in both awareness and usage of flipbook applications. The study concludes that targeted professional development and better access to digital resources are essential for increasing the adoption of flipbook-based learning management. Recommendations include offering training programs to enhance teachers' skills in designing and implementing digital-based learning management using flipbook applications.